Addressing Infection Risk in Veterinary Practice through the Innovative Application of Interactive 3D Animation Methods. (2nd January 2021) - Macdonald, Alastair S.; Chambers, Mark A.; La Ragione, Roberto; Wyles, Kayleigh; Poyade, Matthieu; Wales, Andrew; Klepacz, Naomi; Kupfer, Tom R.; Watson, Fraje; Noble, Shona
Abstract: Antimicrobial resistance is of growing concern in human and animal health. The aim of this study was to raise awareness and perception of risk of infection-related behaviours during routine preparation for veterinary surgery. We took a multi-disciplinary and multi-method approach to 'make visible, the invisible' by illustrating how microbial contamination can be spread during the preparation process for surgical procedures. The design-led visualization approach enhanced inter-disciplinary team and workshop participant contributions during the co-development of an innovative digital tool to support training for veterinary practitioners and students. After experiencing the intervention, 92% of 51 participants agreed to change their behaviour and stated an intention to implement an infection control behaviour that aligned with training objectives. The 3D graphics enhanced the delivery of training content by making difficult and abstract contamination concepts easy to understand. A similar approach could be taken for human health applications.